PERAN MEDIATOR DALAM MENYELESAIKAN KONFLIK SUAMI ISTRI (Studi Kasus Di Pengadilan Agama Kelas 1A Lamongan) - Ahmad Mu’adz Asmuni Assidiqi; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This thesis is the result of the author's research and thoughts entitled "The Role of the Mediator in Resolving Husband and Wife Conflict (Case Study in the Lamongan Class 1A Religious Court)". This research aims to answer the questions stated in the problem formulation. The type of research that the author uses is qualitative, this research uses field research, namely where the author goes directly into the field to obtain objective data at the Lamongan Religious Court. The subjects of this research are Mediator at the Lamongan Religious Court, numbering 17 divided into two. groups, namely 11 mediators from judges and 6 mediators from non-judges. The research object that the author will examine is "The role of mediators in resolving husband and wife conflicts in the Lamongan Religious Courts". Blood collection methods through observation, interviews and documentation. Data analysis The deductive method is a data analysis that starts from general knowledge and then draws specific and specific conclusions. The inductive method is a data analysis that starts from specific facts, concrete events, then from specific and concrete facts or events, then from the specific and concrete facts or events in generalizations that have general nature.The results of this research are that the Mediator at the Lamongan Religious Court schedules a schedule of cases that have been registered and then the litigants will be called according to the schedule queue, the Mediator requires the parties to carry out mediation. Even though the defendant or plaintiff is accompanied by their respective Legal Counsel, the Mediator encourages them to play a direct or active role in the mediation process, the judge is obliged to postpone the trial to give the parties the opportunity to undergo mediation, mediators are obliged to explain the mediation procedures in this Perma to the parties in dispute, then the mediation process accompanied by the mediator will be carried out.